Description of a new snake eel Ophichthus olivaceus (Teleostei: Anguilliformes, Ophichthidae) from the Red Sea - Mccosker, John E.; Bogorodsky, Sergey V.; Mal, Ahmad O.; Alpermann, Tilman J. (Zootaxa, 2020)
A new species of snake eel Ophichthus olivaceus is described based on two specimens trawled from a depth of 35–63 m from a soft substratum off Jizan, Red Sea coast of southern Saudi Arabia. It differs from its congeners by the following combination of characters: vertebrae 141–145; tail moderately short (2.15 in TL); head short (9.6–11.1 in TL); uniserial teeth in jaws and on vomer; pectoral fins slightly elongate, not lanceolate, upper rays longer than the lower; dorsal-fin origin above middle of pectoral fin; and a generally uniform, dark tan body with an olivaceous hue shading to tan or pale orange ventrally, with two pale yellow blotches above pectoral-fin base, snout and lower jaw dark brown, and olivaceous median fins. Its divergence from other mitochondrial-analyzed species is shown by phylogenetic analysis of the mitochondrial COI barcoding region. A key to the Indian Ocean species is provided.